MAINTAINING MOUNTAIN BIKES : THE DO-IT-YOURSELF GUIDE - Allwood, Melanie; Brook, Nigel (Buffalo, New York : Firefly Books, 2010)
More riders than ever are heading to the country on their mountain bikes. It's a sport that has exploded over the last twenty years, as people of all ages and walks of life are drawn to the thrill of the ride.
"Revised and updated. Suitable for all models''--cover.
Keywords: Mountain bikes -- Maintenance and repair